Development of genome-wide insertion/deletion markers and genetic diversity in Sipunculus nudus along the Beibu Gulf of China - Ni, Yuzhu; Han, Chunli; Liu, Yating; Li, Manman; He, Weijie; Yang, Jialin; Zou, Jie; Peng, Huijing; Wang, Pengliang (Frontiers in Genetics, 2025)
Sipunculus nudus, a marine species of substantial medicinal and commercial importance, requires genetic enhancement to boost its production yield. However, progress in genetic research and selective breeding has been constrained by two critical limitations: the scarcity of available molecular markers and the absence of systematic genetic diversity assessments across China’s Beibu Gulf. To address these challenges, our genome-wide investigation identified 168,771 InDel variations, from which we developed 25,558 primer pairs. Experimental validation showed 82 out of 85 synthesized primers (96.47%) successfully amplified target regions, with 81 demonstrating polymorphism. Sixteen high polymorphic markers were subsequently employed to analyze 153 samples collected along the Beibu Gulf coastline, revealing 142 distinct alleles. The number of alleles, effective number of alleles, observed heterozygosity, expected heterozygosity, Shannon’s index and polymorphic information content ranged from 4 to 15 (mean of 8.875), 2.110 to 6.009 (mean of 4.110), 0.009 to 0.768 (mean of 0.232), 0.526 to 0.834 (mean of 0.734), 0.919 to 2.085 (mean of 1.576), and 0.440 to 0.816 (mean of 0.692), respectively. Population structure analysis revealed four genetically distinct subpopulations within the Beibu Gulf population. This delineation of population substructure provides critical insights for optimizing selective breeding programs and formulating germplasm conservation strategies in S. nudus.